A group of adolescent girls' perceptions of HIV/AIDS and the impact of these perceptions on their sexual practices and development - Khutsoane, Magauta Mirriam (My University, 2008)
HIV/AIDS is prevalent among adolescent youth in South Africa particularly among adolescent girls. Numerous efforts have been made to contain the pandemic through HIV prevention information in schools and through community and mass media campaigns, but all these efforts seem not to have an impact on the sexual behaviour of the youth. Reports from various studies concluded that although these programmes increase adolescents’ knowledge they have a minimal impact on their sexual behaviour. The current study explores perceptions of HIV/AIDS among a group of adolescent girls (between 14 and 19 years old) as well as the impact of these perceptions on their sexual practices and development. The results revealed that perceptions of HIV/AIDS appear to have an impact on adolescent girls’ sexual practices.
Keywords: HIV/AIDS; Adolescent girls' sexual behaviour; Transmission of HIV; Perceptions